(untitled) (Nigerian Journal of Physiological Sciences, 2021)
Summary: The study was conducted to investigate safety associated with prolonged consumption of Moringa oleifera leaves as beverage. Fourteen rats were used in this study. They were divided into 2 groups each containing 7 rats. Rats in group I received 2ml/kg of corn oil (standard vehicle drug). Animals in groups II were administered with 400mg/kg body of methanolic extract of Moringa oleifera (MEMO) for five weeks respectively. Serum collected was analyzed for alanine aminotransferase (ALT), aspartate aminotransferase (AST), total protein, albumin, globulin, blood urea nitrogen (BUN) and creatinine. There was significant (P<0.05) decrease in serum total protein, albumin, globulin and AST activity. The activity of ALT decreased but not significant. Similarly, 400mg/kg body of MEMO led to significant (P<0.05) decrease in serum BUN and creatinine. All experimental animals that received 400mg/kb of MEMO had significant (P<0.05) decrease in body weight from week to week 4 of the experiment. Taken together, 400mg/kg body of MEMO seemed to be toxic to the liver with apparently no toxicity in the kidney. Hence, prolonged exposure is not advisable as such could portend danger to the liver.